Heat-shrinkable multilayer film
By adopting a three-layer heat shrinkable multilayer film, using hydrocarbon-based resin, ethylene-based resin and acrylic-based copolymer resin, combined with appropriate resin ratio, the existing heat shrinkage rate, sebum whitening and The problem of high manufacturing cost achieves efficient heat shrinkage and suitable ultrasonic welding.
Patent Information
- Application Number
- CN202380050029.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-05
- Filing Date
- 2023-06-07
- Publication Date
- 2025-02-14
AI Technical Summary
The existing heat shrinkable film has insufficient heat shrinkage at 90°C and contains a relatively high proportion of cyclic olefin resin, which makes sebum whitening difficult to control and high manufacturing cost, and is not suitable for ultrasonic welding.
The heat shrinkable multilayer film adopts a three-layer structure. The surface layer contains hydrocarbon-based resin, ethylene-based resin and acrylic-based copolymer resin. The intermediate layer also contains these resins, but does not contain cyclic olefin-based resin or its content is lower than that of the surface layer. , suitable for ultrasonic welding.
It achieves high heat shrinkage, inhibits sebum whitening, reduces manufacturing costs, and is suitable for ultrasonic welding, improving the application performance of the film.
Smart Images

Figure CN119451820A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heat-shrinkable multilayer film. Background Art
[0002] Patent document 1 discloses a low-temperature heat shrinkable film whose transparency and glossiness are not impaired even after heat shrinkage. The two surface layers of the low-temperature heat shrinkable film disclosed in Patent document 1 are composed of a resin composition obtained by mixing 50 to 150 parts by weight of petroleum resin and / or terpene resin and 50 to 800 parts by weight of polyolefin-based thermoplastic elastomer with respect to 100 parts by weight of polypropylene-based resin, and the middle layer is composed of polyethylene-based resin. According to Patent document 1, the transverse heat shrinkage rate of the low-temperature heat shrinkable film disclosed in Patent document 1 after immersion in hot water at 90°C for 10 seconds is 47%.
[0003] Patent Document 2 also discloses a multilayer heat-shrinkable film. According to Patent Document 2, the multilayer heat-shrinkable film disclosed in Patent Document 2 has a transverse heat shrinkage rate of 50% or more after being immersed in hot water at 90° C. for 10 seconds.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2003-136650
[0007] Patent Document 2: International Publication No. 2004 / 110750 Summary of the invention
[0008] Problems to be solved by the invention
[0009] Although the heat shrinkable film disclosed in Patent Document 1 is considered to have good heat shrinkage at a temperature of 90°C, from a practical point of view, it is preferred that the heat shrinkage rate at 90°C is higher. On the other hand, although the heat shrinkage rate of the heat shrinkable film disclosed in Patent Document 2 is sufficiently high at a temperature of 90°C, the content of cyclic olefin resin is relatively high, especially in the surface film layer and the back film layer. Therefore, not only is sebum whitening difficult to control, but the manufacturing cost is increased. In addition, this heat shrinkable film is used as a substrate for a tubular label that often needs to be sealed at both ends and installed on a container, but the heat shrinkable films disclosed in Patent Documents 1 and 2 do not consider the applicability to ultrasonic welding.
[0010] The object of the present invention is to provide a heat-shrinkable multilayer film which not only has a relatively high heat shrinkage rate but also suppresses sebum whitening, has a low manufacturing cost, and is suitable for ultrasonic welding.
[0011] Methods for solving problems
[0012] The heat-shrinkable multilayer film according to the first aspect of the present invention comprises a pair of surface layers and an intermediate layer disposed between the pair of surface layers. The surface layers contain a total of 45 parts by weight or more of one or more thermoplastic resins selected from hydrocarbon resins, ethylene resins and propylene copolymer resins, relative to a total of 100 parts by weight of the thermoplastic resins contained in the surface layers, and do not contain cyclic olefin resins or contain more than 0 and less than 55 parts by weight of cyclic olefin resins, wherein the hydrocarbon resins are one or more selected from petroleum resins, terpene resins and rosin resins. The intermediate layer contains one or more thermoplastic resins selected from hydrocarbon resins, ethylene resins and propylene copolymer resins, and does not contain cyclic olefin resins or contains cyclic olefin resins in a manner that the content ratio of cyclic olefin resins relative to a total of 100 parts by weight of the thermoplastic resins contained in the intermediate layer is lower than the content ratio of cyclic olefin resins in the surface layer, wherein the hydrocarbon resins are one or more selected from petroleum resins, terpene resins and rosin resins.
[0013] The heat shrinkable multilayer film according to the second aspect of the present invention is the heat shrinkable multilayer film according to the first aspect, wherein the surface layer contains the cyclic olefin resin.
[0014] The heat shrinkable multilayer film according to the third aspect of the present invention is a heat shrinkable multilayer film according to the first or second aspect, wherein the surface layer contains 1 part by weight or more of the cyclic olefin resin relative to 100 parts by weight of the total thermoplastic resin contained in the surface layer.
[0015] The heat shrinkable multilayer film according to the fourth aspect of the present invention is the heat shrinkable multilayer film according to any one of the first to third aspects, wherein the intermediate layer contains the cyclic olefin resin.
[0016] Effects of the Invention
[0017] According to the present invention, it is possible to provide a heat-shrinkable multilayer film which has a relatively high heat shrinkage rate, suppresses sebum whitening, has a low production cost, and is suitable for ultrasonic welding. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1A Schematic diagram of the cross section of the heat-shrinkable multilayer film.
[0019] Figure 1B It is a schematic cross-sectional view of a printed film including a heat-shrinkable multilayer film.
[0020] Figure 2 This is a diagram for explaining a method for producing a heat-shrinkable tubular label (mainly a printing region forming step).
[0021] Figure 3 A diagram for explaining a method for producing a heat-shrinkable tubular label.
[0022] Figure 4 This is a flow chart showing the flow of a method for producing a heat-shrinkable tubular label.
[0023] Figure 5 A diagram for explaining a process of forming an overcoat region.
[0024] Fig. 6A It is a schematic cross-sectional view of the overlapping portion.
[0025] Figure 6B It is a schematic cross-sectional view of the overlapping portion of a modified example.
[0026] Figure 7 A diagram for explaining a sealing method using an ultrasonic welding device.
[0027] Fig. 8A Schematic diagram of the cross section of the sealing line.
[0028] Figure 8B Schematic diagram of the cross section of the sealing line of a modified example.
[0029] Fig. 9 Schematic diagram of the cross section of the label area of a modified example.
[0030] Fig.10 A diagram illustrating defects in the sealing line. DETAILED DESCRIPTION
[0031] Hereinafter, the heat shrinkable multilayer film and the method for producing the heat shrinkable tubular label including the multilayer film of the present invention will be described with reference to the accompanying drawings. It should be noted that the following drawings are appropriately partially deformed for the convenience of description and do not necessarily reflect the actual size and ratio thereof.
[0032] <1.Outline>
[0033] Figure 1A The cross-sectional schematic diagram shows the structure of a heat-shrinkable multilayer film 10 (hereinafter also referred to as "film 10"). The film 10 mainly contains a thermoplastic resin and is suitable for use as a base material of a heat-shrinkable tubular label 1 (hereinafter also referred to as "tubular label 1") as described later (refer to Figure 3 ). Typically, the tubular label 1 is a shrink label attached to the outside of a plastic container including a plastic bottle, a metal container, a glass container, or the like.
[0034] The film 10 is an olefin film having an olefin resin as a main component as a thermoplastic resin, and is configured so that the specific gravity as a whole is less than 1. Examples of the olefin resin include hydrocarbon resins such as petroleum resins, terpene resins, and rosin resins, ethylene resins, propylene resins, cyclic olefin resins, and mixed resins obtained by mixing at least two of these resins.
[0035] like Figure 1A As shown, the film 10 of the present embodiment is a three-layer structure, including a pair of surface layers 12 and an intermediate layer 11 disposed between the pair of surface layers 12. In the present embodiment, each surface layer 12 is laminated adjacent to the front and back sides of the intermediate layer 11. The intermediate layer 11 and the surface layer 12 respectively mainly contain the above-mentioned olefin resin. In addition, the surface layers 12 of the present embodiment respectively constitute the outer side surfaces of the film 10. Hereinafter, one surface of the film 10 constituted by the surface layer 12 is referred to as the first surface 120, and the surface on the back side of the first surface 120 is referred to as the second surface 121. The following describes each layer.
[0036] <2. Surface>
[0037] The surface layer 12 comprises one or more thermoplastic resins selected from hydrocarbon resins, ethylene resins and propylene copolymer resins. The hydrocarbon resins are one or more thermoplastic resins selected from petroleum resins, terpene resins and rosin resins. Moreover, cyclic olefin resins may be further included. Each resin is described below.
[0038] [Petroleum resin]
[0039] Petroleum resin is a resin obtained by polymerizing the C4-C5 fraction (mainly C5 fraction), C5-C9 fraction (mainly C9 fraction) or a mixture thereof remaining after ethylene, propylene, butadiene, etc. are removed by thermal cracking of naphtha. Specifically, alicyclic petroleum resins from cyclopentadiene or its dimer, aromatic petroleum resins from C9 components, and their copolymers, etc. can be cited. From the viewpoint of inhibiting the softening of the film 10 at below 100°C and ensuring transparency and rigidity, hydrogenated alicyclic petroleum resins having an alicyclic structure partially or completely hydrogenated are preferred. In addition, products obtained by refining and polymerizing a single or multiple components of the C5 fraction, C9 fraction, etc. can also be used in the same manner.
[0040] The petroleum resin preferably has a number average molecular weight of 500 to 1000, more preferably 600 to 900 as measured by GPC (gel permeation chromatography). By setting the number average molecular weight within the above range, the rigidity of the film 10 can be increased.
[0041] The softening point of the above-mentioned petroleum resin is preferably above 80°C and below 170°C, and more preferably above 110°C and below 155°C. When the softening point is lower than 80°C, the heat resistance of the film 10 is reduced, and the petroleum resin component may easily seep out to the surface under high temperature conditions. When the softening point exceeds 170°C, the molding processability such as extrusion film forming and stretching processability may deteriorate. On the other hand, when the softening point is above 110°C, the natural shrinkage of the film 10 can be suppressed, and when it is below 155°C, it can be stretched uniformly in the stretching process, so it is preferred. In particular, when the softening point is above 120°C and below 140°C, good thermal shrinkage can be exhibited. The softening point of the petroleum resin is a value measured by a method according to JIS K2207:2006.
[0042] The density of the petroleum resin is preferably 950 kg / m 3 Above, 1050kg / m 3 Below, more preferably 980kg / m 3 Above, 1020kg / m 3 When the density of the petroleum resin is within the above range, the rigidity of the film 10 can be increased.
[0043] When the petroleum resin is a mixed resin containing two or more petroleum resins having different softening points, the softening point of the petroleum resin is an apparent softening point calculated by summing the products of the softening points of the respective petroleum resins and the mass % ratios. The same applies to the density.
[0044] Examples of commercially available products of the commercially available petroleum resins include I-MARV (manufactured by Idemitsu Kosan Co., Ltd.), ARKON (manufactured by Arakawa Chemical Industries, Ltd.), and Regalite (manufactured by Eastman Co., Ltd.).
[0045] [Terpene resin, etc.]
[0046] Examples of the terpene resin include terpene resins derived from α-pinene or β-pinene, copolymers of α-pinene and β-pinene, etc., aromatic modified terpene resins, terpene-phenolic resins, and hydrogenated terpene resins. Examples of the rosin-based resin include gum rosin, wood rosin, tall oil rosin, esterified rosin modified with glycerin or pentaerythritol, etc., and hydrogenated rosin-based resins.
[0047] [Vinyl resin]
[0048] As the ethylene resin, linear low-density polyethylene, branched low-density polyethylene, ethylene-vinyl acetate copolymer, ionomer resin or a mixture thereof can be cited. In addition, copolymers of ethylene and α-olefins can also be cited as the ethylene resin. As α-olefins, there is no particular limitation, and 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc. can be cited, and two or more α-olefins can also be included. The copolymer can be a random copolymer or a block copolymer. In addition, ethylene elastomers, etc. can also be included in the ethylene resin.
[0049] The Vicat softening temperature of the ethylene resin is preferably 45° C. or higher and 120° C. or lower, more preferably 50° C. or higher and 110° C. or lower, and further preferably 55° C. or higher and 100° C. or lower.
[0050] The melt flow rate (MFR, g / 10 min) of the ethylene resin is preferably 1.0 or more and 6.0 or less, more preferably 1.5 or more and 5.0 or less, and even more preferably 2.0 or more and 4.0 or less.
[0051] The density of the ethylene resin is preferably 850 kg / m 3 Above, 950kg / m 3 Below, more preferably 870kg / m 3 Above, 920kg / m 3 the following.
[0052] When the above-mentioned ethylene resin is a mixed resin containing two or more ethylene resins with different Vicat softening temperatures, the Vicat softening temperature of the above-mentioned ethylene resin is the apparent Vicat softening temperature calculated by multiplying the Vicat softening temperature of each ethylene resin with the product of mass % ratio. In addition, density and MFR are also the same.
[0053] Examples of commercially available products of the ethylene-based resin include EVOLUE (manufactured by Primen Polymer Co., Ltd.), UMERIT (manufactured by Ube Maruzen Polyethylene Co., Ltd.), SUMIKATHENE (manufactured by Sumitomo Chemical Co., Ltd.), and NOVATEC (manufactured by Japan Polyethylene Co., Ltd.).
[0054] [Propylene copolymer resin]
[0055] As the propylene copolymer resin, it is preferably a propylene binary copolymer resin or a propylene ternary copolymer resin with propylene as the main component and α-olefin as the copolymer component, and it is particularly preferably a propylene ternary random copolymer resin. The proportion of α-olefin as the copolymer component is preferably 1 to 10 mol%. In addition, the propylene copolymer resin can also be a mixture of different propylene-α-olefin random copolymers. α-olefin is as described above. In addition, the propylene copolymer resin can also contain propylene elastomers, etc.
[0056] The propylene copolymer resin improves the heat shrinkage of the film 10. In addition, the propylene copolymer resin has a lower melting point than homopolypropylene, thereby improving the weldability of the contact interface of the seal line 101. In addition, the surface roughness is reduced, thereby suppressing the damage of the seal portion due to impact such as falling.
[0057] The Vicat softening temperature of the propylene copolymer resin is preferably 55° C. or higher and 135° C. or lower, more preferably 60° C. or higher and 130° C. or lower, and even more preferably 65° C. or higher and 125° C. or lower.
[0058] The melt flow rate (MFR, g / 10 min) of the propylene copolymer resin is preferably 1.0 or more and 8.0 or less, more preferably 2.0 or more and 7.0 or less, and even more preferably 3.0 or more and 6.0 or less.
[0059] The density of the propylene copolymer resin is preferably 850 kg / m 3 Above, 950kg / m 3 Below, more preferably 880kg / m 3 Above, 920kg / m 3 the following.
[0060] When the propylene copolymer resin is a mixed resin containing two or more propylene copolymer resins having different Vicat softening temperatures, the Vicat softening temperature of the propylene copolymer resin is the apparent Vicat softening temperature calculated by summing the product of the Vicat softening temperature of each propylene resin and the mass % ratio. In addition, the density and MFR are also the same.
[0061] [Cyclic olefin resin]
[0062] Cyclic olefin resins can not only reduce the crystallinity of the film 10 and increase the thermal shrinkage, but also improve the stretchability during manufacturing. Examples of cyclic olefin resins include (a) random copolymers of ethylene or propylene with cyclic olefins; (b) ring-opening polymers of the cyclic olefins or copolymers with α-olefins; (c) hydrogenated products of the polymers of (b); (d) grafted modified products of (a) to (c) using unsaturated carboxylic acids and their derivatives.
[0063] The cyclic olefin is not particularly limited, and examples thereof include norbornene, 6-methyl norbornene, 6-ethyl norbornene, 5-propyl norbornene, 6-n-butyl norbornene, 1-methyl norbornene, 7-methyl norbornene, 5,6-dimethyl norbornene, 5-phenyl norbornene, 5-benzyl norbornene and their derivatives. In addition, examples thereof include tetracyclododecene, 8-methyltetracyclo-3-dodecene, 8-ethyltetracyclo-3-dodecene, 5,10-dimethyltetracyclo-3-dodecene, tetracyclododecene and their derivatives. The α-olefin is as described above.
[0064] The number average molecular weight of the cyclic olefin resin measured by GPC method is preferably 1000 to 1,000,000. When the number average molecular weight is within the above range, film formation becomes easy.
[0065] The glass transition temperature of the cyclic olefin resin is preferably 20° C. or higher and 130° C. or lower, and more preferably 50° C. or higher and 100° C. or lower.
[0066] The melt volume rate (MVR, cm 3 The speed (kWh) is preferably 10.0 to 40.0, more preferably 15.0 to 35.0, and even more preferably 20.0 to 30.0.
[0067] When the cyclic olefin resin is a mixed resin containing two or more cyclic olefin resins having different glass transition temperatures, the glass transition temperature of the cyclic olefin resin is an apparent glass transition temperature calculated by summing the products of the glass transition temperatures of the respective cyclic olefin resins and the mass % ratios. The same applies to MVR.
[0068] Examples of commercially available products of the cyclic olefin resin include APEL (manufactured by Mitsui Chemicals, Inc.), TOPASCOC (manufactured by Polyplastics Co., Ltd.), and ZEONOR (manufactured by Nippon Zeon Co., Ltd.).
[0069] [Content ratio]
[0070] The surface layer 12 preferably contains 45 parts by weight or more of the above-mentioned one or more hydrocarbon resins, ethylene resins, and propylene copolymer resins, more preferably 55 parts by weight or more, and even more preferably 65 parts by weight or more, relative to 100 parts by weight of the total thermoplastic resin contained in the surface layer 12. It should be noted that the surface layer 12 only needs to contain at least one of the hydrocarbon resins, ethylene resins, and propylene copolymer resins, and does not need to contain all of these resins.
[0071] In addition, the surface layer 12 may contain the above-mentioned cyclic olefin resin or may not contain the above-mentioned cyclic olefin resin. In the film 10, from the viewpoint of suppressing the whitening of sebum in the part touched by human hands after heat shrinkage and suppressing the cost of the film 10, it is particularly preferred that the surface layer 12 does not contain the above-mentioned cyclic olefin resin (contains 0 parts by weight). In the case where the surface layer 12 contains the above-mentioned cyclic olefin resin, the surface layer 12 preferably contains 1 part by weight or more and less than 55 parts by weight of the above-mentioned cyclic olefin resin relative to a total of 100 parts by weight of the thermoplastic resin contained in the surface layer 12, more preferably contains 1 part by weight or more and 50 parts by weight or less, and further preferably contains 1 part by weight or more and 45 parts by weight or less.
[0072] [Other ingredients]
[0073] In addition, additives such as anti-blocking agents, antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, flame retardants, antibacterial agents, fluorescent brighteners, colorants, etc. may be added to the surface layer 12 as needed.
[0074] <3. Middle layer>
[0075] The middle layer 11 is a layer located on the inner side of the film 10 and is the layer with the largest thickness ratio in the film 10. The middle layer contains one or more thermoplastic resins selected from hydrocarbon resins, ethylene resins, and propylene copolymer resins. The hydrocarbon resin is one or more thermoplastic resins selected from petroleum resins, terpene resins, and rosin resins. In addition, the middle layer 11 may contain cyclic olefin resins or may not contain cyclic olefin resins. Regarding these resins, as described in the description of the surface layer 12, the description is omitted. These resins can use resins of the same composition in the surface layer 12 and the middle layer 11, or resins of different compositions can be used.
[0076] The middle layer 11 only needs to contain at least one of the above-mentioned hydrocarbon resin, ethylene resin and propylene copolymer resin, and does not need to contain all of these resins, but preferably contains hydrocarbon resin and propylene resin. In this case, relative to a total of 100 parts by weight of the thermoplastic resin contained in the middle layer 11, the middle layer 11 preferably contains 5 parts by weight or more and 40 parts by weight or less of the above-mentioned petroleum resin, more preferably 10 parts by weight or more and 35 parts by weight or less, and further preferably 15 parts by weight or more and 30 parts by weight or less. In addition, the middle layer 11 preferably contains 50 parts by weight or more and 95 parts by weight or less of the above-mentioned propylene resin, more preferably 60 parts by weight or more and 90 parts by weight or less, and further preferably 65 parts by weight or more and 85 parts by weight or less.
[0077] It is particularly preferred that the intermediate layer 11 does not contain the above-mentioned cyclic olefin resin (contains 0 parts by weight) like the surface layer 12. On the other hand, the intermediate layer 11 may selectively contain raw materials regenerated from the film 10, intermediate products of the film 10, etc. as recycled raw materials, in which case the above-mentioned cyclic olefin resin may be contained. In the case where the intermediate layer 11 contains the cyclic olefin resin, the intermediate layer 11 contains the above-mentioned cyclic olefin resin in such a manner that the content ratio of the above-mentioned cyclic olefin resin relative to the total 100 parts by weight of the thermoplastic resin contained in the intermediate layer 11 is smaller than the content ratio of the cyclic olefin resin relative to the total 100 parts by weight of the thermoplastic resin contained in the surface layer 12.
[0078] [Other ingredients]
[0079] In addition, additives such as antioxidants, heat stabilizers, ultraviolet absorbers, light stabilizers, lubricants, antistatic agents, flame retardants, antibacterial agents, fluorescent brighteners, colorants, etc. may be added to the surface layer 12 as needed.
[0080] <4.Thickness>
[0081] The total thickness of the film 10 is preferably 20 μm or more and 70 μm or less, more preferably 30 μm or more and 60 μm or less, and further preferably 35 μm or more and 55 μm or less. Moreover, when the thickness of the surface layer 12 is set to 1, the thickness of the intermediate layer 11 is preferably 3 or more and 8 or less, and more preferably 4 or more and 7 or less.
[0082] <5. Thermal shrinkage of film>
[0083] The film 10 is immersed in hot water at 90° C. for 10 seconds, then immediately taken out and immersed in water at 20° C., and then taken out after 10 seconds. Preferably, the heat shrinkage in the TD direction at this time is 50% or more.
[0084] <6. Film production method>
[0085] The method for producing the film 10 is not particularly limited, but preferably the method of simultaneously molding each layer by coextrusion. In the case where the coextrusion method is coextrusion through a T-die, the lamination method may be any of a feed block method, a multi-manifold method, or a combination of the two.
[0086] Specifically, for example, the following method can be cited: the raw materials constituting the intermediate layer 11 and the surface layer 12 are respectively put into an extruder, extruded into a sheet through a die head, and after cooling and solidifying on a pulling roller, stretched in a single axis or a double axis. As the above-mentioned stretching method, for example, a roller stretching method, a tenter stretching method or a combination thereof can be adopted. The stretching temperature is changed according to the softening temperature of the resin constituting the film 10, the shrinkage characteristics required for the film 10, etc., preferably above 65°C and below 120°C, more preferably above 70°C and below 115°C.
[0087] The stretch ratio in the main shrinkage direction is changed according to the resin constituting the film 10, the stretching device, the stretching temperature, etc., and is preferably 3 times or more and 7 times or less, and more preferably 4 times or more and 6 times or less. It should be noted that the MD (machine direction) direction of the film 10 is consistent with the longitudinal direction (second direction), and the TD (transverse direction) direction is consistent with the width direction (first direction). In addition, in the present embodiment, the TD direction is the main shrinkage direction.
[0088] <7. Method for manufacturing tubular label>
[0089] Next, a method for producing the tubular label 1 using the film 10 as a base material will be described. Figure 4 1 is a flow chart showing the flow of a method for manufacturing the tubular label 1 .
[0090] [Preparation process]
[0091] In the method for manufacturing the tubular label 1, first, the film 10 as described above is prepared (step S1). In the present embodiment, the film 10 is prepared in the form of a roll wound in the longitudinal direction, and the roll is mounted on, for example, a conveyor device not shown. The roll is rotated in one direction by such a conveyor device, and the flat film 10 is continuously fed out.
[0092] [Printing area forming process]
[0093] Then, if Figure 2 As shown, while the film 10 is conveyed along the length direction (the direction indicated by the arrow A2) at a certain conveying speed, a plurality of label designs are printed on the first surface 120 using the printing device 4 (step S2). The printing method is flexographic printing, lithographic printing, gravure printing, screen printing, inkjet printing, etc., which are not particularly limited. The printing device 4 is configured to simultaneously print the designs of a plurality of cylindrical labels 1 arranged in the width direction (the direction indicated by the arrow A1) on the conveyed film 10. Thus, the printed film 10A is produced from the film 10.
[0094] The printed film 10A is a film that displays the design of the tubular label 1 and then regularly arranges a plurality of label regions 1A that form each tubular label 1 along the width direction and the length direction. It should be noted that in the figure, only representative examples of the plurality of label regions 1A are marked with symbols. The label region 1A of the present embodiment is configured in such a way that the axial direction of the tubular label 1 is consistent with the length direction, and the circumferential direction is consistent with the width direction.
[0095] The label area 1A of the first surface 120 is configured to include a printing area 13A including one end in the width direction and a non-printing area 13B including the other end in the width direction. It should be noted that in the figure, only representative examples of the plurality of printing areas 13A and non-printing areas 13B are marked with symbols. In the label area 1A of the present embodiment, one end side in the width direction becomes the non-printing area 13B extending in the length direction.
[0096] The printing area 13A is an area formed by laminating one or more ink layers on the first surface 120. On the other hand, the non-printing area 13B is an area that is not laminated with one or more ink layers and remains as a blank portion (see Figure 1B As described above, in each label region 1A, the non-printing region 13B is formed in a manner extending along the length direction at one end side in the width direction. Thus, on the first surface 120 where a plurality of label regions 1A are regularly arranged, a non-printing region 13B extending at least along the length direction is formed.
[0097] [Coating area formation step]
[0098] Next, a coating region 14A is formed on the second surface 121 of the printed film 10A (step S3). The coating region 14A is a region where a coating agent for protecting the second surface 121 is laminated. The coating agent is formed of, for example, a transparent colorless ink called a medium. The coating agent includes a coating agent containing a polyurethane resin and a coating agent containing an acryl resin, and there is no particular limitation. On the other hand, the non-coating region 14B is a region where the coating agent is not laminated and remains as a blank portion (see Figure 1B ).
[0099] like Figure 2 As shown, the label area 1A includes a coating area 14A including one end in the width direction and a non-coating area 14B including the other end in the width direction on the second surface 121. Preferably, the coating area 14A is arranged on the back side of the non-printing area 13B, and the printing area 13A is arranged on the back side of the non-coating area 14B. Figure 2 In the figure, only the representative examples among the plurality of coating regions 14A and non-coating regions 14B are marked with symbols. Figure 3In the figure, for the sake of convenience, the illustration of these contents is omitted.
[0100] The formation of the coating area 14A is as follows Figure 5 As shown, for example, after the printed film 10A can be turned over, the printed film 10A can be carried out while being conveyed in one direction in the same manner as the operation performed in step S2. The formation method of the coating area 14A is not particularly limited, and for example, the coating agent can be applied to the second face 121 by adopting the known coating device 5 used for medium printing. The coating device 5 of the present embodiment is constituted in a manner that a prescribed blank is left in the width direction to apply the coating agent. Thus, the coating area 14A extending in the length direction and the blank portion of the non-laminated coating agent, that is, the non-coating area 14B extending in the length direction are formed on the second face 121.
[0101] [Slit film manufacturing process]
[0102] Next, the printed film 10A after forming the printed area 13A and the overcoating area 14A is slit to produce a plurality of slit films 10B (step S4). The slitting method is not particularly limited as long as it can cut the label area 1A row by row along the length direction. The slit films 10B can also be formed into a form of being wound into a roll along the length direction.
[0103] The slit film 10B thus produced includes a non-printing region 13B continuous in the longitudinal direction at one end in the width direction on the first surface 120 and a non-coating region 14B continuous in the longitudinal direction at the other end in the width direction on the second surface 121 .
[0104] [Transfer start process]
[0105] Next, the slit film 10B is conveyed in the length direction at a certain conveying speed (step S5). For example, a roll of the slit film 10B is mounted on a conveying device (not shown) and the roll is rotated in one direction to continuously feed the planar slit film 10B. Thus, the plurality of label regions 1A of the slit film 10B are conveyed along the length direction. Figure 3 The direction of the middle arrow A2 is sent out in sequence.
[0106] The conveying speed is preferably 100 m / min or more and less than 600 m / min, more preferably 100 m / min or more and 400 m / min or less, and further preferably 100 m / min or more and 200 m / min or less. By setting the conveying speed within the above range, not only the production efficiency can be maintained, but also the sealing strength of the sealing line 101 formed thereafter can be ensured, and the appearance defects such as breakage, wrinkling, and corrugation of the sealing line 101 can be suppressed. It should be noted that, in the present embodiment, the conveying speed of the slit film 10B is consistent with the formation speed of the sealing line 101.
[0107] [Overlapping portion forming step]
[0108] The slit film 10B is conveyed as described above while one end in the width direction overlaps with the other end in a manner that the first surface 120 and the second surface 121 are opposite to each other. Thus, an overlapping portion 100 extending in the length direction is formed (step S6). In this embodiment, the two ends of the slit film 10B are overlapped with each other in a state in which the second surface 121 becomes the outer side surface of the overlapping portion 100 facing the outside and the first surface 120 becomes the inner side surface of the overlapping portion 100 facing the inside. At this time, Fig. 6A As shown, in the overlapping portion 100, the non-printing area 13B and the non-coating area 14B are at least partially opposite to each other.
[0109] Since the sealing line 101 is formed within the range where the non-printing area 13B and the non-coating area 14B are opposite to each other, it is preferred that the relative width of the two areas 13B and 14B is sufficiently larger than the width W1 of the sealing line 101. On the other hand, as long as the relative width of the areas 13B and 14B can be sufficiently ensured, the printing area 13A and the coating area 14A may be included between the first surface 120 and the second surface 121 opposite to each other in the overlapping portion 100.
[0110] [Seal line forming process]
[0111] Next, the slit films 10B in the overlapping portion 100 are continuously ultrasonically welded using an ultrasonic welding device to form a sealing line 101 extending continuously along the length direction (step S7). The ultrasonic welding device of this embodiment includes an oscillator, a vibrator 2, and an anvil 3 (see FIG. 1 ). Figure 7 ). The vibrator 2 includes: a vibrator that vibrates when a predetermined voltage is applied by an oscillator; and an amplifier (horn) that amplifies the amplitude of the vibrator, applies pressure to the welding object, and transmits the vibration of the vibrator. The vibrator 2 is pre-configured at a fixed position on the outer surface side of the overlapping portion 100. As a result, the slit film 10B including the overlapping portion 100 is transported at a constant speed relative to the vibrator 2. The vibrator 2 of this embodiment includes a rotary amplifier that rotates in conjunction with the transport of the slit film 10B.
[0112] The anvil 3 of this embodiment is pre-arranged at a position opposite to the vibrator 2 on the inner surface side of the overlapping portion 100. The anvil 3 is a rigid member that clamps the welding object and receives the pressure from the vibrator 2. In this embodiment, it is configured in the form of a rotating body that rotates in conjunction with the conveyance of the slit film 10B. Figure 7 As shown, the outer peripheral surface 30 of the anvil 3 is formed with projections and depressions. The overlapping portion 100 is conveyed in a state where it is clamped between the vibrator 2 and the anvil 3 and in contact with the outer peripheral surface 30. As a result, a sealing line 101 is formed in the overlapping portion 100, in which the thermoplastic resins of the portion sandwiched between the vibrator 2 and the anvil 3 are welded together. Anvil marks corresponding to the projections and depressions of the outer peripheral surface 30 of the anvil 3 are formed on the sealing line 101. As a result, in the portion sandwiched between the vibrator 2 and the anvil 3, the contact area between the slit films 10B that have melted due to the frictional heat generated by the mechanical vibration is further increased, and the sealing strength is improved.
[0113] As described above, the sealing line 101 is formed in the overlapping portion 100 in a relative range between the non-printing area 13B and the non-coating area 14B. In other words, the sealing line 101 is formed in a manner that does not include the printing area 13A and the coating area 14A between the first surface 120 and the second surface 121 that are opposite to each other. As a result, direct melt mixing of the thermoplastic resin constituting the first surface 120 and the second surface 121 at the interface is promoted, and mixing of printing ink and coating agent as impurities is suppressed. Therefore, the sealing strength of the sealing line 101 can be further improved.
[0114] In addition, the sealing line 101 may not be formed continuously in the entire width direction of the overlapping portion 100, but only needs to be formed continuously in at least a portion of the width direction of the overlapping portion 100. Fig. 8A As shown in FIG. 1 , the seal line 101 is preferably formed in such a manner as to reach at least the outer end 100a of the slit film 10B. Figure 8B As shown, the seal line 101 may not reach the outer end 100a of the slit film 10B, but may be formed between the outer end 100a and the inner end 100b.
[0115] The emission frequency of the vibrator 2 is preferably 20 kHz or more and 40 kHz or less, more preferably 25 kHz or more and 35 kHz or less. By setting the emission frequency of the vibrator 2 within the above range, it is less likely that defects will occur in the sealing line 101 after the tubular label 1 is mounted on the container and heat-shrunk. Defects after heat shrinkage include peeling of the sealing line 101 itself and peeling of the layers of the film 10 in the sealing line 101, which is also referred to as "misalignment" of the sealing line 101 (see Fig.10 ).
[0116] The emission frequency of the vibrator 2 is preferably 20 kHz or more and 40 kHz or less, more preferably 25 kHz or more and 35 kHz or less. By setting the emission frequency of the vibrator 2 within the above range, it is less likely that defects will occur in the sealing line 101 after the tubular label 1 is mounted on the container and heat-shrunk. Defects after heat shrinkage include peeling of the sealing line 101 itself and peeling of the layers of the film 10 in the sealing line 101, which is also referred to as "misalignment" of the sealing line 101 (see Fig.10 ).
[0117] The width (seal width) W1 of the seal line 101 in the width direction is preferably 0.5 mm or more and 15 mm or less, more preferably 1 mm or more and 10 mm or less, and further preferably 2 mm or more and 7 mm or less. By setting the seal width W1 to be greater than the above lower limit, the seal strength of the seal line 101 can be ensured. On the other hand, by setting the seal width W1 to be less than the above upper limit, not only can the good appearance of the tubular label 1 be ensured, but also the tubular label 1 can be manufactured efficiently.
[0118] As described above, when using an anvil 3 having a concave-convex shape on the outer peripheral surface 30, the shape of the concave-convex is not particularly limited, and it is preferred that the arithmetic mean roughness (surface roughness) Ra1 (μm) of the outer side surface 1010 in the sealing line 101 and the arithmetic mean roughness (surface roughness) Ra2 (μm) of the inner side surface 1011 in the sealing line 101 satisfy the relationship Ra1<Ra2. The arithmetic mean roughness Ra (μm) can be measured according to the method of JIS B 0601:2013. It should be noted that the range including the portion where the anvil mark is formed in the sealing line 101 is set as the measurement range, and the reference length along the extension direction of the sealing line 101 is set to 10 mm.
[0119] In addition, from the perspective of suppressing damage to the sealing line 101 due to impact such as falling, the arithmetic mean roughness Ra1 (μm) and the arithmetic mean roughness Ra2 (μm) and the maximum height Rz1 (μm) and the maximum height Rz2 (μm) in the sealing line 101 are preferably smaller.
[0120] The sealing strength (180° peeling force) of the sealing line 101 is preferably 1.5 N / 10 mm or more. When the sealing strength is 1.5 N / 10 mm or more, the above-mentioned defects of the sealing line 101 are not likely to occur even after the tubular label 1 is mounted on the container and heat-shrunk.
[0121] [Coiling process]
[0122] Refer again Figure 4In this embodiment, the slit film 10B with the sealing line 101 and the long cylindrical body is continuously rolled up from the front end by a winding roller (not shown) in a state where the cylindrical body is flattened and folded (step S8). Thus, a long cylindrical body roll with multiple cylindrical labels 1 continuous in the length direction is formed in the winding roller.
[0123] [Transfer completion process]
[0124] The sealing line 101 is formed at the end of the slit film 10B fed out from the material roll. Once the slit film 10B is wound into a long cylindrical body by the winding roller, the delivery of one roll of the slit film 10B is completed (step S9).
[0125] [Cutting process]
[0126] After step S9, the obtained long cylindrical body roll is cut between adjacent cylindrical labels 1 to obtain a plurality of individual cylindrical labels 1 having a sealing line 101 extending in the axial direction (step S10).
[0127] <8. Features>
[0128] In the film 10 of the present embodiment, by not containing cyclic olefin resin, or in particular by making the content ratio of the cyclic olefin resin in the surface layer 12 less than 55 parts by weight, not only can sebum whitening be suppressed, but also the manufacturing cost can be reduced. In addition, by making the surface layer 12 and the intermediate layer 11 contain one or more thermoplastic resins selected from hydrocarbon resins, ethylene resins and propylene copolymer resins, the heat shrinkage rate in 90°C hot water can be made 50% or more. In addition, since the film 10 has the applicability of the sealing method using ultrasonic welding, it can be suitably used as the base material of the tubular label 1.
[0129] The sealing method using ultrasonic welding can be completed without using sealants such as tape and solvents, so it can suppress the emission of greenhouse gases caused by solvents. In the sealing method using solvents, solvent swelling sometimes occurs, and there is also a problem that the sealing line of the folded long cylindrical body and the part opposite to the sealing line are prone to adhesion during the winding process. In the sealing method using ultrasonic welding, adhesion caused by such solvent swelling can be avoided. In addition, since the sealing line 101 of the tubular label 1 does not have a sealant layer between the first surface 120 and the second surface 121 relative to each other, the efficiency and quality of the cycle can be improved.
[0130] On the other hand, in the heat sealing method of applying heat to the slit film 10B, a large amount of heat is required to weld the slit film 10B, and time is also required for cooling after sealing, while in the above method, a large amount of heat and cooling time are not required. Therefore, the above manufacturing method is excellent from the viewpoint of energy saving and manufacturing efficiency.
[0131] <9. Modifications>
[0132] Several embodiments of the present invention have been described above, but the present invention is not limited to the above embodiments, and various changes can be made without departing from the gist thereof. For example, the following changes can be made. In addition, the main points of the following modified examples can also be appropriately combined.
[0133] <9-1>
[0134] The cross-sectional shape of the outer peripheral surface 30 of the anvil 3 is not particularly limited. From the viewpoint of setting the sealing strength of the seal line 101 to a preferred range, the anvil 3 preferably has a plurality of convex portions protruding radially outward of the anvil 3 .
[0135] <9-2>
[0136] The film 10 is not limited to the three-layer structure as described above, and may be, for example, a five-layer structure or a structure having more layers. In addition, the film 10 may be a biaxially stretched film or a uniaxially stretched film.
[0137] <9-3>
[0138] In the above embodiment, the slit film 10B formed into a long cylindrical body with the seal line 101 is wound up by a winding roller. However, the winding step may be omitted and the cylindrical labels 1 may be cut and separated from the front end of the slit film 10B formed into a long cylindrical body to obtain individual cylindrical labels 1.
[0139] <9-4>
[0140] In the above embodiment, the overlapping portion 100 is formed with the first surface 120 as the inner side surface and the second surface 121 as the outer side surface. However, the overlapping portion 100 may also be formed with the first surface 120 as the outer side surface and the second surface 121 as the inner side surface. In this case, as long as Figure 6B As shown, in the overlapping portion 100, the non-printing area 13B and the non-coating area 14B are at least partially opposite to each other and a sealing line 101 is formed within the range where these areas are opposite to each other.
[0141] <9-5>
[0142] The conveying speed of the film 10 refers to the relative speed with respect to the vibrator 2. That is, although the position of the vibrator 2 relative to the conveyed film 10 in the above-mentioned embodiment is fixed, the sealing line 101 can be formed while the vibrator 2 is moved at a certain speed in the longitudinal direction, and the relative conveying speed of the film 10 with respect to the vibrator 2 is not less than 100 m / min and less than 600 m / min.
[0143] <9-6>
[0144] The label region 1A may be arranged so that the axial direction and the width direction of the tubular label 1 coincide with each other, and the circumferential direction and the longitudinal direction coincide with each other.
[0145] <9-7>
[0146] The coating area 14A and the non-coating area 14B may be formed simultaneously with or before the printing area 13A and the non-coating area 13B. The coating area 14A and the non-coating area 14B may be formed without forming the coating area 14A and the non-coating area 14B.
[0147] <9-8>
[0148] In the above embodiment, in the label area 1A, the printing area 13A includes one end in the width direction, and the non-printing area 13B includes the other end in the width direction. However, the arrangement of the printing area 13A and the non-printing area 13B is not limited to this. For example, Fig. 9 As shown, two printing areas 13A of different sizes are formed to include the ends in the width direction, and the non-printing area 13B is arranged at a position biased towards one end in the width direction. In addition, the coating area 14A and the non-coating area 14B can also be formed in a manner that has the same configuration relationship in the second surface 121.
[0149] Example
[0150] Hereinafter, examples of the present invention will be described in detail, but the present invention is not limited to these examples.
[0151] <1. Preparation of Examples and Reference Examples>
[0152] As raw materials for constituting the intermediate layer and the surface layer laminated adjacent to the surfaces of the intermediate layer on both sides, raw materials having the properties shown in Table 1 were mixed in the proportions shown in Table 2 to prepare resin compositions for constituting the intermediate layer and the surface layer of the heat shrinkable films of Examples 1 to 11 and Comparative Example 1.
[0153] [Table 1]
[0154]
[0155] [Table 2]
[0156]
[0157] The resin composition is melted and co-extruded from a T-die according to the resin composition constituting the middle layer and the surface layer, and then cooled and solidified by a roll cooled to 30°C to produce an unstretched resin film. It is stretched to 5 times in the TD direction using a tenter-type stretching machine at a temperature of 95°C to produce a three-layer heat-shrinkable film with a surface layer laminated adjacent to both sides of the middle layer. The overall length, width, thickness, thickness of the middle layer and thickness of the surface layer of the heat-shrinkable film are the same in Examples 1 to 11 and Comparative Example 1, and the thickness ratio of the surface layer / middle layer / surface layer is 1 / 6 / 1. The width direction of each heat-shrinkable film is consistent with the TD direction.
[0158] By forming an ink layer on one surface of the heat shrinkable film, a printed film having a plurality of label designs regularly arranged in the length direction and the width direction is produced. In any printed film, the label area forming a cylindrical label is as follows Figure 2 The printed area includes one end in the width direction and the non-printed area includes the other end. The printed films are cut in the length direction according to the width of the label area divided by a column to produce a cut film with a continuous label area in the length direction. It should be noted that the formation of the overcoating area is omitted.
[0159] The slit films of Examples 1 to 11 and Comparative Example 1 were conveyed to an ultrasonic welding device (ultrasonic sealing device manufactured by DUKANE) at the conveying speed (forming speed) shown in Table 3, and a long cylindrical body having a seal line of 3 mm in width was produced under the conditions (general) shown in Table 3. In each slit film, the overlapping portion was formed so that the surface (first surface) having the printed area was oriented inward, and the seal line was formed in the portion where the first surface and the second surface opposed to each other so as not to include the printed area.
[0160] [Table 3]
[0161]
[0162] <2. Evaluation>
[0163] The heat shrinkable films, long cylindrical bodies, and tubular labels of Examples 1 to 11 and Comparative Example 1 were evaluated as follows.
[0164] <2-1. Thermal shrinkage>
[0165] Cut out 5 samples of 100 mm in TD and 100 mm in MD from any part of the heat shrinkable film of Examples 1 to 11 and Comparative Example 1. Immerse each sample in 90°C hot water for 10 seconds, then immediately take it out and immerse it in 20°C water, and take it out after 10 seconds. Then measure the length L (mm) of each sample in TD direction, and calculate the shrinkage rate (%) in TD direction according to the following formula. For the heat shrinkable film of Examples 1 to 11 and Comparative Example 1, the average shrinkage rate of each sample is taken as the heat shrinkage rate.
[0166] Shrinkage (%) = {(100-L) / 100}×100
[0167] The thermal shrinkage rate was evaluated as follows.
[0168] Rating A: Heat shrinkage is 50% or more (sufficient heat shrinkage)
[0169] Rating B: Thermal shrinkage is less than 50% (inadequate thermal shrinkage)
[0170] <2-2. Seal strength>
[0171] Five cylindrical samples with a length of 10 mm in the longitudinal direction were cut from the long cylindrical bodies of Examples 1 to 11 and Comparative Example 1, and the opposite sides of the sealing line were cut to make rectangular samples of about 20 cm with the sealing line arranged in the center. The peeling force in the 180° direction was measured using a peel strength tester (HEIDON TYPE17, manufactured by Shinto Scientific Co., Ltd.) using the samples, and the average value of the five samples was taken as the sealing strength of Examples 1 to 11 and Comparative Example 1. The preferred sealing strength is 1.5 N / 10 mm or more.
[0172] <2-3. Surface roughness of the sealing line>
[0173] Five flat samples of the portion including the sealing line were cut out from the long cylindrical bodies of Examples 1 to 11 and Comparative Example 1. For these samples, the surface roughness of the outer side surface and the surface roughness of the inner side surface of the sealing line were measured in accordance with JIS B 0601: 2013 (reference length 10 mm). Based on these measured values, the average values of the five samples were calculated and used as the surface roughness Ra1 (μm) of the outer side surface and the surface roughness Ra2 (μm) of the inner side surface.
[0174] <2-4. Maximum height of the sealing line>
[0175] According to the long cylindrical bodies of Examples 1 to 11 and Comparative Example 1, the maximum height of the outer side surface and the maximum height of the inner side surface of the sealing line of each sample were measured (reference length 10 mm). Based on these measured values, the average value of the five samples was calculated as the maximum height Rz1 (μm) of each outer side surface and the maximum height Rz2 (μm) of each inner side surface.
[0176] <2-5. Appearance inspection of sealing line>
[0177] Five cylindrical samples were cut out from each of the long cylindrical bodies of Examples 1 to 11 and Comparative Example 1, and the seal lines were checked for damage, wrinkles, and ripples. The appearance evaluation was as follows.
[0178] Rating A: No damage, wrinkles, or ripples were confirmed in all five samples.
[0179] Rating B: A sample in which at least one of breakage, wrinkling, and ripples was observed.
[0180] <2-6. Misalignment test after heat shrinkage>
[0181] Five cylindrical samples with a folding diameter of 108.5 mm and a length of 100 mm in the longitudinal direction were cut out from the long cylindrical bodies of Examples 1 to 11 and Comparative Example 1 as cylindrical labels. They were covered on a conventional PET bottle for beverages (with the lid closed). First, the lower end of the cylindrical label was immersed in boiling water at 100°C for 1 second. After the cylindrical label was fixed on the PET bottle, the entirety was immersed in boiling water for 30 seconds in a manner such that the cylindrical label was not misaligned with the PET bottle. Then, the cylindrical label was cut open with a cutting tool, removed from the PET bottle, and the water was wiped off. The folded parts caused by the shape of the PET bottle were removed from the cut cylindrical label, and a sample containing a sealing line was cut out. The sample was pasted on a backing paper with double-sided tape, and a microscope was used to confirm whether there was any misalignment of the sealing line. The evaluation of misalignment is as follows.
[0182] Rating A: No misalignment was confirmed in all samples.
[0183] Rating B: There are samples in which misalignment is confirmed.
[0184] <2-7. Cold resistance bending and dislocation test>
[0185] Four cylindrical samples with a folding diameter of 108.5 mm and a length of 100 mm in the longitudinal direction were cut out from the long cylindrical bodies of Examples 1 to 11 and Comparative Example 1, respectively, as cylindrical labels. These cylindrical labels were placed in a constant temperature and humidity chamber set at 5°C for 1 hour. Then, under the same environment, the sealing line of each cylindrical label was held in a manner of clamping, and the longitudinal direction was bent within the range of -90° to 90°, and bent 20 times. After the bending action was performed evenly at 4 locations in the longitudinal direction of the sealing line, the constant temperature and humidity chamber was set to an environment of 23°C and 50% RH, and each cylindrical label was placed therein for 1 hour. Then, each cylindrical label was covered on a normal PET bottle for beverages (with the lid closed), and the lower end of the cylindrical label was first immersed in boiling water at 100°C for 1 second. After the cylindrical label was fixed on the PET bottle, the entirety was immersed in boiling water for 10 seconds in a manner that the cylindrical label was not misaligned with the PET bottle. Then, the seal line was observed with a microscope in the same manner as the displacement test after heat shrinkage to confirm whether there was displacement. The evaluation of displacement was the same as the displacement test after heat shrinkage.
[0186] <2-8. Heat resistance bending dislocation test>
[0187] The cylindrical labels of Examples 1 to 11 and Comparative Example 1 were prepared in the same manner as the misalignment test after heat shrinkage and the cold-resistant bending misalignment test. Under an environment of 23°C, the sealing line of each cylindrical label was bent 20 times at 5 locations in the length direction according to the same method as the cold-resistant bending misalignment test. Then, each cylindrical label was covered on the glass bottle, and a hot cyclone shrinking device (Tornado 2001, manufactured by Nippon Technology Solution Co., Ltd.) was used to shrink and install the cylindrical label on the glass bottle under the conditions of a residual heat section temperature of 140°C, an air volume of 30Hz, a heating section of 250°C, an air volume of 40Hz, and an air duct passing time of 33s. Among them, the direction of the glass bottle in the hot cyclone shrinking device was adjusted so that the hot air could directly blow against the sealing line of the cylindrical label.
[0188] Then, the cylindrical label is cut open with a cutting tool and removed from the glass bottle, and the length W2 of the resulting seal line misalignment along the length direction is measured (refer to Fig.10 ). Wherein, when the dislocation is generated discontinuously along the length direction, the sum of the lengths W2 of the dislocations at each location is taken as the dislocation length. The same test is performed 20 times, and the average value of the dislocation length (the sum of the lengths W2) is calculated. The evaluation of the dislocation length is as follows.
[0189] Rating A: The misalignment length is less than 10 mm (misalignment is suppressed).
[0190] Rating B: The misalignment length is 10 mm or more (misalignment easily occurs).
[0191] <2-9. Resistance to sebum whitening>
[0192] The evaluation of resistance to sebum whitening is as follows. Samples with a size of 150 mm in the longitudinal direction and 250 mm in the transverse direction are cut out from the heat-shrinkable films of Examples 1 to 11 and Comparative Example 1, and two marking lines are marked in the longitudinal direction, so that the spacing between the marking lines is 150 mm. The above-mentioned samples that have been touched multiple times with fingertips with sebum on the wing of the nose attached are immersed in hot water at 80°C for 7 seconds, thereby shrinking the spacing between the marking lines to 135 mm, and then evaluated as A or B in the order of the good (less) degree of sebum whitening. That is, rating A indicates relatively high fat resistance, and rating B indicates that the fat resistance does not meet the standard.
[0193] <3. Evaluation results>
[0194] The evaluation results are shown in Table 4 below.
[0195] [Table 4]
[0196]
[0197] In Examples 1 to 11, a heat shrinkage of 50% or more was obtained, and good results were obtained in that there were no problems with the peeling force and appearance of the sealed part, and sebum whitening was well controlled. Thus, it was confirmed that even if a large amount of expensive cyclic olefin resin is not contained, a heat-shrinkable multilayer film with a sufficiently high heat shrinkage and applicability to ultrasonic welding and sebum whitening is not likely to occur after heat shrinkage can be obtained. However, in the evaluation of the heat-shrinkable film of Example 11 after it was made into a cylindrical label and installed on a bottle, the seal line was misaligned. On the other hand, although Comparative Example 1 had no problems in terms of heat shrinkage, peeling force of the sealed part, appearance, and misalignment after bottle installation, sebum whitening was confirmed.
[0198] Explanation of symbols
[0199] 1 cylindrical label
[0200] 2 vibrators
[0201] 3 Anvil
[0202] 10 Heat shrinkable film
[0203] 10A Printed film
[0204] 10B Slitting Film
[0205] 11 Middle Layer
[0206] 12 Surface
[0207] 13A Printing Area
[0208] 13B Non-printing area
[0209] 30 Outer Surface
[0210] 100 Overlap
[0211] 101 Sealing Line
[0212] 120 Page 1
[0213] 121 Second Side
[0214] 1010 Outer side
[0215] 1011Inner side.
Claims
1. A heat shrinkable multilayer film, characterized in that: comprising a pair of surface layers and an intermediate layer disposed between the pair of surface layers, The surface layer contains 45 parts by weight or more of one or more thermoplastic resins selected from hydrocarbon resins, ethylene resins and propylene copolymer resins, relative to 100 parts by weight of the total thermoplastic resins contained in the surface layer, and does not contain cyclic olefin resins or contains more than 0 and less than 55 parts by weight of cyclic olefin resins, wherein the hydrocarbon resins are selected from one or more of petroleum resins, terpene resins and rosin resins. The intermediate layer contains one or more thermoplastic resins selected from hydrocarbon resins, ethylene resins and propylene copolymer resins, and does not contain cyclic olefin resins or contains cyclic olefin resins in a manner such that the content ratio of cyclic olefin resins relative to a total of 100 parts by weight of the thermoplastic resins contained in the intermediate layer is lower than the content ratio of cyclic olefin resins in the surface layer, and the hydrocarbon resins are one or more selected from petroleum resins, terpene resins and rosin resins.
2. The heat-shrinkable multilayer film according to claim 1, wherein: The surface layer contains the cyclic olefin-based resin.
3. The heat-shrinkable multilayer film according to claim 2, wherein: The surface layer contains 1 part by weight or more of the cyclic olefin-based resin based on 100 parts by weight of the total thermoplastic resin contained in the surface layer.
4. The heat-shrinkable multilayer film according to claim 3, characterized in that: The intermediate layer contains the cyclic olefin-based resin.
Citation Information
Patent Citations
Low temperature heat-shrinkable multilayered film excellent in transparency and glossiness
JP2003136650A
Multilayer heat-shrinkable film and containers fitted with labels made from the film through heat shrinkage
WO2004110750A1